2017
DOI: 10.1038/s41598-017-09697-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Tumor Induction in the Zebrafish

Abstract: The zebrafish has become an increasingly popular and valuable cancer model over the past few decades. While most zebrafish cancer models are generated by expressing mammalian oncogenes under tissue-specific promoters, here we describe a method that allows for the precise optical control of oncogene expression in live zebrafish. We utilize this technique to transiently or constitutively activate a typical human oncogene, kRASG12V, in zebrafish embryos and investigate the developmental and tumorigenic phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…We decided to use our optogenetics approach to address that issue. Carcinogenesis was investigated in zebrafish through the initiation of the expression of a single oncogene (kRasG121V) in two‐ to three‐day‐old embryos . We showed that transient activation of the oncogene (Figure A–C) did not result in cancer (Figure A–C), whereas permanent activation (Figure D–F) led in some cases to tumors (Figure D–F), albeit with a very low probability (ca.…”
Section: The Caged‐cyclofen‐oh/ert Systemmentioning
confidence: 96%
See 3 more Smart Citations
“…We decided to use our optogenetics approach to address that issue. Carcinogenesis was investigated in zebrafish through the initiation of the expression of a single oncogene (kRasG121V) in two‐ to three‐day‐old embryos . We showed that transient activation of the oncogene (Figure A–C) did not result in cancer (Figure A–C), whereas permanent activation (Figure D–F) led in some cases to tumors (Figure D–F), albeit with a very low probability (ca.…”
Section: The Caged‐cyclofen‐oh/ert Systemmentioning
confidence: 96%
“…To achieve transient genetic activation, we used a fusion between the ERT domain and a transcription factor (Gal4) that can similarly be activated by cyclofen‐OH uncaging . Diffusion of the transcription factor to the nucleus activates genes under control of a UAS promoter.…”
Section: The Caged‐cyclofen‐oh/ert Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of spatial control include the use of tissue-specific promotors, [11] and examples of temporal control include using heat-shock-induced Cre recombinase expression [12] or the addition of 4-hydroxy tamoxifen to translocate a Cre–estrogen receptor fusion protein (Cre–ER) to the nucleus. [13] Both spatial and temporal control were achieved by using a photocaged 4-hydroxy tamoxifen analogue [14] with a Cre–ER-expressing fish line. [15] However, Cre–ER fusions have shown activation in the absence of 4-hydroxytamoxifen, and although this is reduced by certain mutants of ER, such as Cre–ER T2 , some background activity is still possible.…”
mentioning
confidence: 99%